Circulating SFLT-1 is placentally derived in normal pregnancy - Cerdeira, A; Kandzija, N; Burdujan, A; Zhang, W; Motta-Mejia, C; White, K; Gill, M; Cooke, W; Thammasate, B; Ri, R; Pargmae, P; James, T; et al. (Elsevier, 2018)
Excess hypoxia can lead to developmental abnormalities and antenatal deficits such as fetal intrauterine growth restriction and preeclampsia. Capillary pericytes are multifunctional cells wrapped around the vascular endothelium that play essential roles in vascular development and blood flood regulation. In vivo, brain pericytes respond to hypoxia by irreversibly constricting capillaries and thus causing cell death in rigor. To date, placental capillary pericytes (PLVP) have not been fully characterized in placenta biology. We aimed to investigate the effects of hypoxia on human PLVP.